2016
DOI: 10.4236/jeas.2016.61001
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of L-Ascorbic Acid by Spray Drying Using Sodium Alginate as Wall Material

Abstract: L-ascorbic acid is a water soluble vitamin (vitamin C) widely used as an additive in foods and cosmetics. It has high instability against certain environmental factors; the main cause of its deterioration is oxidation. Microencapsulation is an effective protection technique of L-ascorbic acid from its degradation reactions. This work is focused on the encapsulation of L-ascorbic acid by spray drying technique using sodium alginate as wall material. The microcapsules morphology was observed by scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…The moisture content of microcapsule is also influenced by the type and composition of encapsulant which can hinder evaporation. The increase of encapsulant composition that is not accompanied with inlet temperature increase can cause low evaporation rate (Sormoli et al, 2012;Marcela et al, 2016). Different result had been reported by Fazaeli et al (2012), the moisture content of microcapsules was decreased with addition of encapsulant concentration.…”
Section: Moisture Contentmentioning
confidence: 98%
See 1 more Smart Citation
“…The moisture content of microcapsule is also influenced by the type and composition of encapsulant which can hinder evaporation. The increase of encapsulant composition that is not accompanied with inlet temperature increase can cause low evaporation rate (Sormoli et al, 2012;Marcela et al, 2016). Different result had been reported by Fazaeli et al (2012), the moisture content of microcapsules was decreased with addition of encapsulant concentration.…”
Section: Moisture Contentmentioning
confidence: 98%
“…Sormoli et al (2012) reported that glass transition temperature increases along with the increase of encapsulant concentration, which relates with the increase of polymer bond between the types of encapsulant used in lactose drying using spray dryer. Marcela et al (2016) explained that the increase of alginate ratio as an encapsulant and the use of low inlet temperature cause more particles sticky to the walls of the spray dryer's chamber and the particles cannot be removed.…”
Section: Phycocyanin Contentmentioning
confidence: 99%
“…The EY was calculated and expressed as the percentage of total solid of the mixture before encapsulation per weight of the encapsulated SCGE dry basis (db) (Marcela et al, 2016).…”
Section: Encapsulation Yield Determinationmentioning
confidence: 99%
“…The EE was calculated and expressed as the percentage of the TPC differentiation in the encapsulated SCGE and the wall materials used for encapsulation (Marcela et al, 2016).…”
Section: Encapsulation Efficiency Determinationmentioning
confidence: 99%
“…Some studies using spray drying method to process microencapsulation [8,9,10,11] because of its affordable price and the availability of equipment. However, spray drying using high inlet temperature, which can reduce the phycocyanin content.…”
Section: Introductionmentioning
confidence: 99%